Comparative study of high-temperature grain boundary engineering of two powder-processed low stacking-fault energy Ni-base superalloys. (28th June 2016) - Detrois, Martin; McCarley, Joshua; Antonov, Stoichko; Helmink, Randolph C.; Goetz, Robert L.; Tin, Sammy
Abstract : Results of high-temperature grain boundary engineering of an experimental, low stacking-fault energy (LSF) Ni-base superalloy were compared to a commercially available superalloy RR1000. Deformation mechanism maps for thermal-mechanical processing were compared along with the resulting length fractions of Σ3 boundaries following sub-solvus and super-solvus annealing. Compared to the hot deformation processing characteristics of RR1000, lowering the stacking-fault energy reduces dislocation mobility and expands the range of temperatures and strain rates over which dislocation-based plastic flow mechanisms were operative in the LSF alloy. For both alloys, processing conditions conducive to dislocation-based plasticity allowed for the storage of strain energy within the microstructure that was utilised for strain-induced boundary migration (SIBM) and the formation of Σ3 boundaries upon annealing. Based on the results of this study, alloying changes that serve to reduce the stacking-fault energy of Ni-base superalloys also make the alloys more amenable for grain boundary engineering techniques that utilised hot deformation.